Cloning and expression of maize transglutaminase gene in Escherichia coli and its action over dairy proteins. Issue 10 (17th September 2020) - Han, Xiue; Ma, Chunli; Qin, Lanxia; Liu, Lu
Abstract: In this study, total RNA was extracted from young leaves of maize. Reverse transcription‐PCR (RT‐PCR) method was used to obtain full‐length TGase gene. The amplified fragment was sequenced to have 1, 605 bp. The gene consisted of 535 amino acid residues with a calculated molecular mass of 60.9 kD. It was identical to the published TGase gene (GenBank NO.AJ421525). The TGase fragment was cloned into pET‐28a prokaryotic expression vector. The pET‐28a‐TGase was transformed into Escherichia coli competent cells. The expression of TGase was induced and identified with SDS‐PAGE. The recombinant protein with 60 kD was expressed as expected. It concludes that the recombinant TGase was expressed in prokaryotic cell. The inclusion body was extracted and purified with Ni 2+ ‐NTA agarose. The antigenicity of recombinant protein was confirmed with Western Blotting. This study on functional characteristics was also carried out. The recombinant protein has a strong polymerization effect on casein and catalyzed restructured yogurt cross‐linking. Practical applications: Transglutaminase is an effective enzyme that catalyzes the cross‐linking of various food proteins, improves food product quality, and is widely used in the food industry in various processes, as in the manufacture of cheese and other dairy products, in meat products, as in the production of edible films and in the manufacture of bakery products. Moreover, TGase has a wide variety of applications in the pharmaceutical industry, such as the production of antibody‐drug conjugates, in regenerative medicine. It also finds applications in the textile and leather industries, biofilm production, and enzyme immobilization.